ANALISIS PENGARUH IDEALISASI, MOTIVASI INSPIRASI, STIMULASI INTELEKTUAL, KEPERHATIAN INDIVIDU TERHADAP KETERIKATAN KARYAWAN DI LEMBAH KARYA TENUN - Muhammad Sholikhul Huda; Noor Arifin (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the idealization influence, inspirational motivation, intellectual stimulation, and individual attention as dimensions of transformational leadership toward employee engagement at Lembah Karya Tenun Troso. Type of research is quantitative with a Structural Equation Modeling (SEM) approach based on SmartPLS 4 as an analysis tool. The research sample was 75 respondents who were permanent employees of Lembah Karya Tenun. The results of the analysis show that three of the four dimensions of transformational leadership have a positive and significant effect to employee engagement, namely inspirational motivation (T-statistic = 2.853; P = 0.004), intellectual stimulation (T-statistic = 3.211; P = 0.001), and individual attention (T-statistic = 6.850; P = 0.000). Meanwhile, the idealization influence of leader has no significant effect (T-statistic = 0.441; P = 0.659). Value of R-square of 0.870 indicates that the model has high predictive power. These findings indicate that inspirational motivation, intellectual stimulation, individual attention are the key factors increasing on employee engagement.